2016
DOI: 10.1371/journal.pone.0165572
|View full text |Cite
|
Sign up to set email alerts
|

Allium sativum Protease Inhibitor: A Novel Kunitz Trypsin Inhibitor from Garlic Is a New Comrade of the Serpin Family

Abstract: PurposeThis study was aimed to purify and characterize the Protease inhibitor (PI) from a plant Allium sativum (garlic) with strong medicinal properties and to explore its phytodrug potentials.MethodsAllium sativum Protease Inhibitor (ASPI) was purified using ammonium sulphate fractionation and Fast Protein Liquid Chromatography on anion exchanger Hi-Trap DEAE column. The purified protein was analyzed for its purity and molecular weight by SDS PAGE. The confirmation of presence of trypsin inhibiting PI was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The protein PI-QT exhibited inhibitory effects against trypsin and α-chymotrypsin with specific activities of 975 ± 26 and 417 ± 14 U/mg, respectively. The specific activity of the protein PI-QT was comparable with that of novel serpins reported in recent studies [21][22][23][24] . For example, Jiang et al 21 have cloned and expressed a novel serpin (Spi1C) from metagenomic library of uncultured marine microorganisms; the Spi1C protein exhibited inhibitory effects against trypsin and α-chymotrypsin with specific values of 6940 and 3640 U/mg, respectively.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The protein PI-QT exhibited inhibitory effects against trypsin and α-chymotrypsin with specific activities of 975 ± 26 and 417 ± 14 U/mg, respectively. The specific activity of the protein PI-QT was comparable with that of novel serpins reported in recent studies [21][22][23][24] . For example, Jiang et al 21 have cloned and expressed a novel serpin (Spi1C) from metagenomic library of uncultured marine microorganisms; the Spi1C protein exhibited inhibitory effects against trypsin and α-chymotrypsin with specific values of 6940 and 3640 U/mg, respectively.…”
Section: Discussionsupporting
confidence: 83%
“…Chan et al 22 have purified a thermostable trypsin inhibitor from small pinto beans and reported that the purified protein showed inhibitory activity against trypsin with specific value of 2398 U/mg. Shamsi et al 23 have isolated and purified a novel Kunitz trypsin inhibitor (ASPI) from garlic Allium sativum; the ASPI protein showed inhibitory activity against trypsin with specific activity of 30376 U/mg. In another study, Mohan et al 24 purified and characterized a protease inhibitor from Capsicum frutescens with specific activity against trypsin of 6749 U/mg.…”
Section: Discussionmentioning
confidence: 99%
“…The three CsKPI proteins suppress the activity of trypsin and reduce the formation rate of the PNA reaction product (Fig. 3b, c), which mirrors the activities of KPIs from other plant species 40,41 . In addition, the inhibitory activities of the CsKPI2 and CsKPI3 mutant proteins were nearly abolished after two key residues (Arg and Lys) were replaced with alanine, suggesting that these two residues have essential roles in the inhibition of PIs (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 53%
“…The partially purified soybean meal extract unexpectedly processed DL-BApNA, indicating that it contained a measurable level of amidolytic activity (Shamsi et al, 2016). This finding suggests the presence of proteases in the soybean meal preparation, a feature that could be of benefit for the purposes of this work, given that Cry and Cyt proteins digested by insect endo-proteases may exhibit increased insecticidal activity (Vidal-Quist et al, 2010).…”
Section: Discussionmentioning
confidence: 76%